Establishment and validation of a three-dimensional finite element model for degenerative lumbar scoliosis - Guo, Wei; Yang, Wanzhong; Yang, Jie; Zhao, Xin; Zhang, Honglai; Wang, Zemin; Wang, Shiyong; Ma, Rong; Ge, Zhaohui (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveThe objective of this study was to construct a three-dimensional finite element model of degenerative lumbar scoliosis (DLS) and validate its effectiveness, providing a reliable theoretical tool for optimizing surgical plans and biomechanical research.MethodsA 3D finite element model (FEM) of Lenke-Silva type IV DLS was constructed from patient CT data using Mimics, Geomagic Warp, SolidWorks, and ANSYS, incorporating cortical bone, cancellous bone, and intervertebral discs with defined material properties and contact relationships. Geometric validation was performed by comparing vertebral alignment and offset with radiographic measurements, while biomechanical validation involved applying a 400N axial load and 7.5 Nm torque (flexion/extension, lateral bending, and axial rotation) to L1 and comparing the results with established literature data.ResultsThe successfully constructed L1-S1 DLS finite element model comprised 1,255,696 tetrahedral elements (1.5 mm mesh size) and 1,919,710 nodes. Geometric validation demonstrated excellent agreement with radiographic measurements, showing <1 error in Cobb and lumbar lordosis, and <1.76 mm deviation in vertebral centroid alignment. Biomechanical validation revealed that the segmental range of motion (ROM) at L2-3 through L4-5 under 7.5 Nm loading conditions (flexion/extension, lateral bending, and axial rotation) matched established literature data, confirming model reliability.ConclusionThe DLS three-dimensional finite element model constructed in this study exhibits high anatomical fidelity and biomechanical reliability, enabling dynamic simulation of spinal mechanical behavior under complex loads, thereby providing an experimental foundation for surgical plan optimization and complication prediction.